Pengaruh Dukungan Organisasi Dan Keterikatan Karyawan Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. PLN (Persero) UPT Padang - Zani, Ariessa; Sari , Vivi Nila; Sari , Desi Permata (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This research examines how much influence organisational support and employee engagement have on employee performance with job satisfaction as an intervening variable at PT. PLN (Persero) UPT Padang. The research results showed that there was a significant influence of organisational support on job satisfaction. There is a significant influence of employee engagement on job satisfaction. There is a significant influence of organisational support on employee performance. There is a significant influence of employee engagement on employee performance. There is a significant influence of job satisfaction on employee performance. Job satisfaction mediates the effect of organizational support on employee performance. Job satisfaction mediates the effect of employee engagement on employee performance